Fostering STEM Learning: Exploring the Integration of Design Thinking in Islamic STEM Education - Elbashir, Abubaker M.; Alkhair, Shahad; Al-Thani, Noora J. (QiST: Journal of Quran and Tafseer Studies, 2024)
This study investigates the integration of Design Thinking in STEM education within an Islamic context, focusing on thermal packaging as a learning module. The research examines differences in STEM Interest, Design Thinking skills, and Subject Knowledge across 7th and 8th-grade students, as well as the relationships between these constructs. A quantitative approach was employed, involving 64 preparatory students from an institute of religious studies in Qatar. Participants engaged in a Design Thinking-based STEM workshop on thermal packaging, followed by a comprehensive survey assessing the three key constructs. The Independent-Samples Mann-Whitney U Test revealed no significant differences between grade levels for STEM Interest (U = 424.500, p = .434), Design Thinking skills (U = 494.000, p = .843), or Subject Knowledge (U = 469.500, p = .873). However, bivariate correlation analysis showed strong positive relationships among the constructs for both grade levels. For 7th-grade students, STEM Interest and Design Thinking Skills were strongly correlated (r = 0.856), while 8th-grade students showed a robust correlation between Design Thinking Skills and Subject Knowledge (r = 0.884). These findings suggest that integrating Design Thinking approaches in STEM education within an Islamic context can effectively enhance students' interest, skills, and knowledge simultaneously. The study highlights the potential of Design Thinking-based STEM workshops to create a synergistic learning environment that aligns with Islamic principles and values while preparing students for contemporary challenges. The research contributes to the growing body of literature on culturally responsive STEM education and provides insights for educators seeking to bridge traditional Islamic teachings with modern technological advancements.